Association of change in muscle mass assessed by D3‐creatine dilution with changes in grip strength and walking speed. Issue 1 (17th October 2019) - Duchowny, Kate A.; Peters, Katherine E.; Cummings, Steven R.; Orwoll, Eric S.; Hoffman, Andrew R.; Ensrud, Kristine E.; Cauley, Jane A.; Evans, William J.; Cawthon, Peggy M.; ,
Abstract: Background: Muscle mass declines with age. However, common assessments used to quantify muscle mass are indirect. The D3 ‐creatine (D3 Cr) dilution method is a direct assessment of muscle mass; however, longitudinal changes have not been examined in relation to changes in other measures of muscle mass, strength, and performance. Methods: A convenience sample of 40 men from the Osteoporotic Fractures in Men Study (mean age = 83.3 years, standard deviation = 3.9) underwent repeat assessment of D3 Cr muscle mass, dual‐energy X‐ray absorptiometry (DXA) lean mass, grip strength, and walking speed at two time points approximately 1.6 years apart (2014–2016). One‐sample t ‐tests and Pearson correlations were used to examine changes in DXA total body lean mass, DXA appendicular lean mass/height 2, DXA appendicular lean mass/weight, D3 Cr muscle mass, D3 Cr muscle mass/weight, grip strength, walking speed, and weight. Results: D3 ‐creatine muscle mass, D3 Cr muscle mass/weight, grip strength, and walking speed all significantly declined (all P < 0.01). The change in DXA measures of lean mass was moderately correlated with changes in D3 Cr muscle mass. There was no significant correlation between the change in DXA measures of lean mass and change in walking speed (all P > 0.05). The change in D3 Cr muscle mass/weight was moderately correlated with change in walking speed ( r = 0.33, P < .05). The change in grip strength was weakly correlated with the change in DXA measures of lean mass and D3 Cr muscle mass ( r = 0.19–0.32). Conclusions: The results of our study provide new insights regarding the decline in muscle strength and D3 Cr muscle mass. The D3 Cr method may be a feasible tool to measure declines in muscle mass over time.